1977
DOI: 10.1159/000212167
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cardiovascular Pathology and Hearing Loss in the Aged

Abstract: With the objective of studying a possible correlation between chronic cardiovascular disturbances and hearing loss in aged people, two groups were compared. The first was composed of apparently healthy subjects and the second, of subjects suffering from clinically evident chronic cardiovascular pathology. All the subjects were submitted to a pure tone audiometry, discrimination test, SISI test and TDT. The results showed a significant difference in pure tone threshold audiometry between the apparently healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…[21][22][23] The seminal clinical investigation relating these entities was performed by Gates and colleagues. 24 A strong relationship was found between low-frequency hearing thresholds and cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] The seminal clinical investigation relating these entities was performed by Gates and colleagues. 24 A strong relationship was found between low-frequency hearing thresholds and cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…While many of the studies looked mainly into hearing thresholds, that by Rubinstein et al [1977] found no difference in word discrimination percentage between patients with or without cardiovascular symptoms, although lower pure tone average was recorded among patients with cardiovascular symptoms. This could imply a cochlear, and not a retrocochlear (central), origin of the impairment.…”
Section: Evidence Of Neural Effectmentioning
confidence: 99%
“…Hearing loss is a widespread, underrecognized health problem in older adults 1 . Age‐related hearing loss has been associated with many factors, including noise exposure, genetic predisposition, systemic diseases such as cardiovascular disease and diabetes mellitus, ear‐related diseases, medication ototoxicity, socioeconomic status, and lifestyle factors 2–21 …”
mentioning
confidence: 99%
“…1 Age-related hearing loss has been associated with many factors, including noise exposure, genetic predisposition, systemic diseases such as cardiovascular disease and diabetes mellitus, ear-related diseases, medication ototoxicity, socioeconomic status, and lifestyle factors. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Hearing loss prevalence increases dramatically with age. In U.S. studies, prevalence estimates of hearing loss at birth are approximately 0.5%, 22 and in children, approximately 5%.…”
mentioning
confidence: 99%